Appropriateness criteria for the use of cardiac computed tomography, SIC-SIRM part 2: acute chest pain evaluation; stent and coronary artery bypass graft patency evaluation; planning of coronary revascularization and transcatheter valve procedures; cardiomyopathies, electrophysiological applications, cardiac masses, cardio-oncology and pericardial diseases evaluation. Issue 5 (May 2022) - Carrabba, Nazario; Pontone, Gianluca; Andreini, Daniele; Buffa, Vitaliano; Cademartiri, Filippo; Carbone, Iacopo; Clemente, Alberto; Guaricci, Andrea Igoren; Guglielmo, Marco; Indolfi, Ciro; La Grutta, Ludovico; Ligabue, Guido; et al.
Abstract : In the past 20 years, cardiac computed tomography (CCT) has become a pivotal technique for the noninvasive diagnostic workup of coronary and cardiac diseases. Continuous technical and methodological improvements, combined with fast growing scientific evidence, have progressively expanded the clinical role of CCT. Randomized clinical trials documented the value of CCT in increasing the cost-effectiveness of the management of patients with acute chest pain presenting in the emergency department, also during the pandemic. Beyond the evaluation of stents and surgical graft patency, the anatomical and functional coronary imaging have the potential to guide treatment decision-making and planning for complex left main and three-vessel coronary disease. Furthermore, there has been an increasing demand to use CCT for preinterventional planning in minimally invasive procedures, such as transcatheter valve implantation and mitral valve repair. Yet, the use of CCT as a roadmap for tailored electrophysiological procedures has gained increasing importance to assure maximum success. In the meantime, innovations and advanced postprocessing tools have generated new potential applications of CCT from the simple coronary anatomy to the complete assessment of structural, functional and pathophysiological biomarkers of cardiac disease. In this complex and revolutionary scenario, it is urgently needed to provide an updated guide for the appropriate use of CCT in different clinical settings. This manuscript, endorsed by the Italian Society of Cardiology (SIC) and the Italian Society of Medical and Interventional Radiology (SIRM), represents the second of two consensus documents collecting the expert opinion of cardiologists and radiologists about current appropriate use of CCT.